Electronic spectral parameters and IR nonlinear optical features of novel Ag 0.5Pb 1.75GeS 4 crystal - Kogut, Yu; Khyzhun, Oleg Yu; Parasyuk, Oleg V.; Ali Hussain, Reshak, Prof. Dr.; Lakshminarayana, Gandham; Kityk, Iwan V.; Piasecki, Michał M. (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/